Konseling Trait and Factor untuk Meningkatkan Self Confidence Siswa - Muslima Muslima (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The purpose of this study was to find out the application of Trait and Factor counseling in increasing the Self-Confidence of students at MTsN 4 Pidie and SMP Negeri 4 Sakti, by helping students to increase their self-confidence in the learning process at school and outside of school. Knowing the condition of students' self-confidence is still at a low level, counseling is given to increase self-confidence. The research method used was pre-experimental designs with one group pretest-posttest design. The results of the study showed that students with low self-confidence, lacked focus during PBM, students were passive and indifferent during the teaching and learning process, were not enthusiastic about participating in school activities, there were still many students who cheated when there were assignments. But problems can be overcome by providing Trait and Factor counseling, students are given treatment through Trait and Factor counseling with self-confidence material. The results obtained were an increase in scores from the initial pretest and posttest results at the end.